(NgORODA I GODY(B: [(NrOMAN(B] /s (N~ASTX (B1s - (NfEDIN(B, (NkONSTANTINs ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1982)
(Nw (B1 (NTOM WYDA@]EGOSQ SOWETSKOGO PISATELQ k(B.(Na(B. (NfEDINA (B(1892-1977) (NWHODIT ROMAN (B"(NgORODA I GODY(B".s
rus
Keywords: (NkLASSI^ESKAQ PROZAs; (NrOMANs